The Influence of Social Media Marketing on Purchase Impulses with Brand Attentiveness as A Mediating Variable on UMKM X - Sutisna, Felix; Handra, Tessa; Jap, Yustina Peniyanti (Aptisi Transactions On Technopreneurship (ATT), 2023)
The purpose of this study was to analyze the effect of social media marketing on purchase impulses mediated by brand attentiveness. This research has three variables, namely social media marketing, brand attentiveness, and purchase impulse. The sample in this study was 231 customers of UMKM X. The method of analysis in this study was SEM partial least squares (PLS) analysis. PLS-SEM analysis was carried out through secondary data collection and hypothesis testing. The results showed that all 4 hypotheses were significant.